Islamic revolution 1978-1979 years and social-political development of Iran. - Dzhakubaeva S. Т. (Journal of Oriental Studies, 2016)
In this article is given detailed analysis to events 1978-1979 years, which took place in Iran, and which still didn’t receive the assessment in the history. Studied social, economic, and political changes occurring during revolution in the Iranian society. And also is considered degree of study of this problem in russian and foreign monographs. In article is defi ned the orientation, the importance of Islamic revolution. Also are analyzed changes in the Iranian society, which occurred after revolution.